Analysis of Medication Compliance in Hypertension Patients at the Cempaka Putih District Health Center, Jakarta - Yohanes Gamayana Trimawang Aji; Natalia Natalia; Yenny Yenny (Pelopor Publikasi Akademika, 2023)
Hypertension is characterized by an increase in blood pressure that is systolic (above 140 mmHg) and diastolic (above 90 mmHg), both of which are above the normal range. This can be seen in the medical records of the most hypertension sufferers from March to May as many as 758 respondents. This incident was caused by several things, one of which was non-compliance in taking drugs in Cempaka Putih Health Center patients. This study aims to determine the description of adherence to medication in hypertensive patients. This researcher uses quantitative with descriptive design. The number of samples in this study was 88 which were obtained through convenience sampling and data collection using a questionnaire. The results of this study showed that adherence to medication in hypertensive patients was obedient as many as 67 people (76.1%). Based on gender, namely female. Based on the elderly age above 56 years as many as 38 people (43.2%). Based on the level of education, namely high school graduates as many as 46 people (52.3%). Based on religion, namely Islam as many as 76 people (86.4%). Based on marital status that is married as many as 64 people (72.7%). Based on the work that is not working as many as 49 people (55.7%). Based on the distance of health services that is 1 km as many as 78 people (88.6%). Based on the length of suffering from hypertension that is > 5 years as many as 68 people (77.3%). Based on the number of drugs consumed, namely single as many as 88 people (100%). Based on the type of drug consumed, namely amlodipine as many as 82 people (93.2%).